Net Profit Margin sebagai Indikator Kinerja Keuangan Industri Agrifood Subsektor Peternakan Unggas Terintegrasi di Bursa Efek Indonesia - Kharisma Fitri Hapsari (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
The integrated poultry agrifood subsector plays a strategic role in Indonesia’s national economy and food security. However, it faces significant challenges arising from fluctuations in feed raw material prices, particularly corn and soybean meal, which directly affect corporate profitability. This study aims to analyze and compare the profitability performance of integrated poultry agrifood companies listed on the Indonesia Stock Exchange during the 2019–2024 period, using Net Profit Margin (NPM) as the primary indicator. The research adopts a descriptive quantitative approach through financial ratio analysis, utilizing secondary data obtained from the financial statements and annual reports of five companies: PT Charoen Pokphand Indonesia Tbk, PT Japfa Comfeed Indonesia Tbk, PT Malindo Feedmill Tbk, PT Sreeya Sewu Indonesia Tbk, and PT Widodo Makmur Unggas Tbk. The results indicate that companies with larger business scale and higher levels of vertical integration tend to achieve higher and more stable NPM values throughout the observation period. Firms such as CPIN and JPFA were able to maintain positive NPM despite rising feed cost pressures during the 2021–2023 period, while companies with lower cost efficiency exhibited more volatile and even negative NPM. These findings highlight that efficient feed cost management, reflected in NPM stability and supported by value chain integration and technology-based operational efficiency, is a key determinant of sustainable profitability in the integrated poultry agrifood subsector amid volatile input prices.